Profitability of Broiler Production on Diets Containing Ground Peanut (Arachis hypogaea) Shell as a Potential Alternative Feed Ingredient - Moniño, Analyn M.; Ibañez, Jr. , Roger Y.; Moniño, Primitivo D. (Future Science / FSH-PH Publications, 2023)
The study investigated the effects of incorporating ground peanut shells into broiler diets on growth performance, feed conversion efficiency, and production cost. The results showed that broilers fed diets with ground peanut shells had improved growth performance and body weight compared to those without. Moreover, the inclusion of ground peanut shells in broiler diets improved feed conversion efficiency, indicating a reduction in the amount of feed required for broiler growth. The findings suggest that ground peanut shells can be used as a safe and effective feed ingredient for broilers without compromising their health and survival. The utilization of agricultural by-products such as peanut shells in the poultry industry can have significant benefits. Incorporating ground peanut shells into broiler diets can reduce production expenses while providing essential nutrients for human consumption. This can result in an increase in income for households involved in poultry raising. Furthermore, the use of agricultural by-products can contribute to reducing environmental waste, leading to a more sustainable and environmentally friendly poultry industry. The study highlights the potential of utilizing agricultural by-products such as peanut shells in the poultry industry. Incorporating ground peanut shells into broiler diets can reduce production costs, increase income for households involved in poultry raising, and provide essential nutrients for human consumption.